Assessment of Run-of-River and Hydropower Plants in Peru: Current and Potential Sites, Historical Variability (1981–2020), and Climate Change Projections (2035–2100) - Gutierrez, Leonardo (2025)
Hydropower is the main source of renewable energy and the most feasible for implementation in remote areas without access to conventional energy grids. Therefore, knowledge of actual, potential, and future perspectives of sustainable hydropower projects is decisive for their viability. This study aims to estimate the present and future potential capacity of Peru’s hydropower system and from the potential small hydroelectric plants, specifically Run-of-River class. First, we employed geospatial databases and hydroclimatological products to describe the current hydropower system and potential sites for Run-of-River projects. The findings identified 11,965 potential sites for Run-of-River plants. Second, we executed and validated a hydrological model to estimate historical daily streamflows (1981–2020) and hydropower parameters for actual and potential sites. It was determined there is an installed capacity of 5.2 GW in the current hydropower system and a total potential capacity of 29.1 GW for Run-of-River plants, mainly distributed in the northern and central Andes. Finally, we evaluated future changes driven by ten global climate models under three emission scenarios (SSP1-2.6, SSP3-7.0, and SSP5-8.5), compared with the baseline period of 1981–2010 with two future time slices. The main results about capacity indicated that operational hydroelectric plants (Run-of-River plants) are projected to decrease by 0.5 to −5.4% (−7.2 to −2.2%) during 2036–2065 and by −9.2 to 3.8% (1.8 to −11.9%) during 2071–2100. These outcomes provide relevant information to support policymakers in addressing sustainable development gaps in the coming decades and stakeholders involved in the implementation and mitigation of climate change impacts on hydropower projects in Peru.